High-manganese aluminum bronze alloy and preparation method thereof
By controlling the element content and optimizing the microstructure in aluminum bronze alloys, the problem of aluminum bronze alloys is solved, and the high strength, hardness and corrosion resistance are improved, and are suitable for marine engineering.
Patent Information
- Application Number
- CN202411708077.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-28
AI Technical Summary
Existing aluminum bronze alloys are easily oxidized and corroded in marine environments, and their mechanical properties and corrosion resistance are not enough to meet the high requirements in the field of marine engineering.
By controlling the element content, especially the proportions of Al, Mn, Fe, and Ni, in the aluminum bronze alloy, the microstructure of the ingot is optimized, the size and number of needle-shaped phases are controlled, and the optimized distribution of α, β and κ phases are formed.
It realizes the high strength, hardness and corrosion resistance of high manganese aluminum bronze alloy, and has excellent impact toughness, and is suitable for parts and materials in the field of marine engineering.
Smart Images

Figure CN119530607A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of copper alloy materials, and in particular relates to a high manganese aluminum bronze alloy and a preparation method thereof. Background Art
[0002] Aluminum bronze is a copper-based alloy with aluminum as the main added element. Its mechanical properties are better than those of brass and tin bronze, especially when the aluminum content is about 8%. It has good mechanical strength, wear resistance, seawater corrosion resistance and cold resistance. Therefore, aluminum bronze is widely used in aerospace, marine engineering and mining equipment. Although aluminum bronze can show excellent corrosion resistance in the atmosphere and fresh water, due to the active chemical properties of aluminum, aluminum bronze is easily oxidized in air or humid environment, forming an oxide film on the surface of aluminum bronze. In the marine environment, due to the presence of chloride ions, it is easy to destroy the oxide film on the surface of aluminum bronze and produce pitting, affecting the corrosion resistance of aluminum bronze. Secondly, in the special application scenarios in the field of marine engineering, the comprehensive performance requirements for ship accessories are getting higher and higher, and ordinary aluminum bronze alloy materials can no longer meet the needs of the field.
[0003] To address the above problems, researchers have added Mn, Fe, and Ni elements to aluminum bronze alloys, and continuously optimized and improved the process to make them have high strength, good fracture toughness, resistance to seawater cavitation corrosion, and resistance to seawater corrosion. These alloys are widely used in propellers and other materials. However, these improvements have not reduced the negative impacts of these improvements, such as loose internal structure of the alloy, the appearance of pores in the alloy, and other defects, which lead to decreased mechanical properties of the alloy and poor corrosion resistance.
[0004] Based on this, there is an urgent need to develop an aluminum-bronze alloy with excellent mechanical properties such as strength and toughness and improved corrosion resistance, so as to improve the overall quality level of aluminum-bronze alloys, meet the higher requirements for aluminum-bronze materials in various fields, and increase service life, especially in the field of marine engineering. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a high manganese aluminum bronze alloy and a preparation method thereof in view of the deficiencies in the prior art. The high manganese aluminum bronze has high strength and hardness, and at the same time has excellent corrosion resistance and impact toughness, and can be used in the field of marine engineering.
[0006] The technical solution adopted by the present invention to solve the above technical problems is: a high manganese aluminum bronze alloy, the mass percentage composition of the aluminum bronze alloy contains Mn: 11.5-14.5wt%, Al: 7.0-8.5wt%, Fe: 2.5-4wt%, Ni: 1.5-2.5wt%, C≤0.03wt%, and the balance is Cu and inevitable impurities. In the cross-sectional microstructure of the aluminum bronze alloy ingot, the average width of the needle phase structure is ≤1μm, and the average length is ≤20μm.
[0007] The aluminum bronze alloy of the present invention is mainly added with Al, which is a core corrosion-resistant and strengthening element in the aluminum bronze alloy. It can form an oxide film on the alloy surface to promote surface passivation, and can also promote the formation of high-hardness β phase and κ phase, as well as refine the grains, reduce the number and size of micropores in the alloy, and further improve the strength, hardness, corrosion resistance and toughness of the alloy. When the Al content is lower than 7.0wt%, there is only a single-phase α structure in the alloy. At this time, the alloy has high plasticity and toughness and is easy to form, but the hardness and strength are low. With the increase of Al content, the grains can be refined, and the β phase appears in the alloy at high temperature to form a (α+β) two-phase aluminum bronze alloy. In the cooling process of the alloy, the κ phase is precipitated in its microstructure, and a part of the β phase is converted into the α phase, and the remaining small amount of the β phase remains unchanged. The formation of the κ phase and the β phase is beneficial to increase the strength, hardness and corrosion resistance of the alloy. When the Al content is greater than 8.5wt%, excessive κ phase and coarsening will be formed, resulting in reduced toughness and corrosion resistance of the alloy. At the same time, excessive Al will cause Al-rich precipitation phase to form at the grain boundary, seriously deteriorating the forging process performance of the alloy. Therefore, the Al content should not be too high. The present invention controls the Al content to 7.0-8.5wt%.
[0008] 11.5-14.5wt% of Mn is added to the aluminum bronze alloy of the present invention. Mn can improve the stability of the β phase, expand the β phase area, reduce the γ2 phase area, and can also improve the melt fluidity of the alloy, improve the alloy strength, and slow down the structural decomposition during the cooling process of the alloy, reduce the micropore defects of the alloy, and use Mn alloying to effectively reduce the alloy cost. The addition of the Mn element in the present invention can avoid the occurrence of the β→α+γ2 eutectoid transformation, thereby avoiding the formation of the γ2 phase, because the formation of the γ2 phase will reduce the strength and toughness of the alloy, causing the corrosion sensitivity of the alloy to increase, which is not conducive to the improvement of corrosion resistance. The addition of the Mn element can prevent the heating cracking and cooling cracking of large forgings, avoid the precipitation of brittle phases, and can also effectively improve the processing performance of the alloy, but too high a Mn content has an adverse effect on the corrosion resistance, so Mn should not be too high. When the Mn content is less than 11.5wt%, an Al-rich phase will be generated, which will reduce the solid solubility of Al in the α phase to a certain extent, which is not conducive to the improvement of the comprehensive performance of the alloy of the present invention. Therefore, the present invention further controls the ratio of the mass percentage of Al to Mn in the aluminum bronze alloy, Al / Mn, within the range of 1:(1.62-1.86). When the Al / Mn content ratio is less than 1:1.86, the alloy structure will be coarsened and loosened, and the probability of the formation of the needle-like phase in the alloy structure will be increased, resulting in reduced strength, toughness and corrosion resistance; when the Al / Mn content ratio is higher than 1:1.62, an excessive amount of Al-rich precipitation phase will be formed, resulting in poor fluidity of the alloy melt, reduced processing performance, and not conducive to the effective improvement of mechanical properties. When the Mn content exceeds 14.5wt%, residues may be generated during the casting process, and the alloy structure may be easily coarsened, especially the high content of Mn elements will cause the alloy to absorb carbon, increase the carbon content in the alloy, and increase and coarse the needle-like phase, which is not conducive to the improvement of the comprehensive performance of the alloy. Therefore, the present invention controls the Mn content to 11.5-14.5wt%.
[0009] 1.5-2.5wt% Ni is added to the aluminum bronze alloy of the present invention. The Ni element can be infinitely dissolved in the copper matrix, and when dissolved in the copper matrix, the strength, hardness and corrosion resistance of the alloy can be improved. Within the appropriate Ni content range, the corrosion resistance of the alloy increases with the increase of the Ni content, because Ni improves the protective performance of the alloy corrosion film layer. The addition of Ni can also prevent excessive precipitation of the γ2 phase in the alloy, thereby avoiding the increase of the alloy's brittleness and the decrease of toughness. In addition, the Ni element dissolved in the α phase can refine the α phase grains. If the Ni content is too high, the alloy strength and hardness are high, the processing difficulty is large and the cost is increased; and if the Ni content is too low, the alloy strength and corrosion resistance are reduced, and the product requirements cannot be met. The present invention controls the Ni content to 1.5-2.5wt%.
[0010] The aluminum bronze alloy of the present invention adds 2.5-4wt% of Fe. As one of the main additive elements, Fe has very low solubility in the aluminum bronze alloy. Although it can refine the grains and improve the mechanical properties of the alloy, excessive Fe addition will form a needle-like phase FeAl3, which will reduce the mechanical properties and corrosion resistance of the alloy. Therefore, the Fe content in the alloy should not exceed 4wt%. Secondly, too low Fe content can accelerate the atomic diffusion rate in the aluminum bronze alloy, reduce the stability of the β phase, and make it difficult to suppress the "self-annealing" phenomenon that causes the alloy to become brittle, greatly increasing the brittleness of the alloy. The appropriate amount of Fe can also refine the casting structure and recrystallized grains of the aluminum bronze alloy, improve the mechanical properties of the aluminum bronze alloy, and is not easy to form a needle-like phase structure, thereby improving the corrosion resistance of the alloy. Therefore, the present invention controls the Fe content to 2.5-4wt%.
[0011] The aluminum bronze alloy of the present invention controls C≤0.03wt%. Excessive C will lead to C increase in the melt after the alloy is subjected to too high alloy melting temperature or too long melting time. During the solidification process, C forms a large number of needle-like phases including (Fe2Mn)C similar to Fe3C with Fe and Mn elements, and the size of the needle-like phase will also increase. The needle-like phase structure has poor bonding strength with the matrix in the alloy, and even cracks will appear, which will lead to the invasion of corrosive liquid and seriously deteriorate the corrosion resistance of the alloy. Secondly, the needle-like phase structure will reduce the impact toughness of the alloy and also have adverse effects on the mechanical properties of the alloy. Therefore, the aluminum bronze alloy of the present invention controls C≤0.03wt%, and C≤0.01wt% is further preferred.
[0012] In the cross-sectional microstructure of the high manganese aluminum bronze alloy ingot of the present invention, the average width of the needle-like phase structure is ≤1 μm, the average length is ≤20 μm, and the number of needle-like phase structures per unit area is ≤5 / 1×10 4 μm 2 The needle-like phase structure precipitated in the aluminum bronze alloy of the present invention will have a negative impact on the comprehensive performance of the alloy, because the needle-like phase structure has poor bonding with the alloy matrix. Large-sized or excessive needle-like phase structures make the alloy prone to cracking and slipping during processing and service. Even large-sized needle-like phase structures will cause holes, resulting in the comprehensive performance of the alloy failing to meet the requirements. Therefore, the present invention controls the size and number of needle-like phase structures, controls the average width to ≤1μm, the average length to ≤20μm, and controls the number of needle-like phase structures per unit area to ≤5 / 1×10 4 μm 2 .
[0013] Preferably, the mass percentage composition of the high manganese aluminum bronze alloy of the present invention also contains at least one element of Cr, S, Si, Pb, O, P, Ti, Zr, Co, B, Mg, Ag, Zn and RE in a total amount not exceeding 2wt%. Adding an appropriate amount of the above elements to the high manganese aluminum bronze alloy of the present invention can significantly refine the alloy structure, further promote the refinement and quantity control of the κ phase, reduce the looseness of the alloy structure, and even reduce the size and quantity of micropores in the microstructure, thereby enhancing the mechanical properties and corrosion resistance of the alloy. The present invention controls the total amount of the above elements within 2wt%. If the content is too high, it cannot further produce a significant strengthening effect, but will reduce the comprehensive performance of the alloy.
[0014] The cross-sectional microstructure of the high manganese aluminum bronze alloy ingot of the present invention mainly contains α phase, β phase and κ phase, wherein the number of κ phases with a size between 0.1 and 10 μm is ≥50 / 1×10 4 μm 2 The κ phase in the aluminum bronze alloy of the present invention is mainly a compound composed of Fe and Al, and the morphology mainly includes petal-shaped or spherical κ i Phase, which belongs to Fe-rich phase, such as Fe3Al phase and FeAl phase. This phase strengthens the comprehensive performance of the alloy by dispersion. Since the coarse κ phase will make the alloy brittle and reduce the comprehensive mechanical properties of the alloy, in addition, the fine κ phase is dispersed around the α phase and β phase, reducing the corrosion rate of the α phase and effectively enhancing the corrosion resistance. However, κ phases that are too small or too large will cause κ phase agglomeration, so that the comprehensive performance of the alloy cannot be effectively improved. Therefore, the number of κ phases with a size between 0.1 and 10 μm in the cross-sectional microstructure of the aluminum bronze alloy of the present invention is ≥50 / 1×10 4 μm 2 .
[0015] In the cross-sectional microstructure of the high manganese aluminum bronze alloy ingot of the present invention, micropores are a strong factor affecting the corrosion resistance of the alloy. On the one hand, micropores will lead to a decrease in strength, toughness and hardness; on the other hand, the copper alloy with pores will form pitting corrosion that is easy to corrode because the pore surface is difficult to clean, and further affect the corrosion resistance of the entire alloy material. Therefore, in the cross-sectional microstructure of the aluminum bronze alloy ingot of the present invention, the micropore size is ≤0.2mm, and the number of micropores per unit area is ≤5 / mm 2 If it exceeds this range, the excessive and large micropores will cause the corrosive liquid to invade the internal structure of the alloy, seriously affecting the improvement of the corrosion resistance of the alloy; on the other hand, the strength, toughness and hardness of the alloy will decrease. During the service of the alloy, micropore defects will cause the alloy to fail prematurely.
[0016] The present invention also relates to a method for preparing the above-mentioned high manganese aluminum bronze alloy. The process flow for preparing the aluminum bronze alloy ingot comprises: smelting → degassing → casting → insulation, wherein the degassing time is not less than 10 minutes, and the casting speed is controlled within 50 mm / min. The specific steps are as follows:
[0017] (1) Melting: The melting temperature of the high manganese aluminum bronze of the present invention is not higher than 1350°C, and the melting temperature of the aluminum block is not higher than 1300°C. In order to further reduce the micropores and control the content of impurity elements, the present invention uses cryolite to cover the copper liquid during the melting process. In addition, 2 kg of sodium fluoride and calcium fluoride mixed salt is added every 30 minutes during the melting of the alloy elements, which can further reduce the number and size of micropores in the alloy and achieve heat preservation. Stir evenly after melting is complete.
[0018] (2) Degassing: The degassing time of the preparation method of the present invention is more than 10 minutes, wherein the degassing adopts a carbon-free gas-filled rod, such as boron nitride, zirconium oxide, etc. The carbon-containing gas-filled rod is not used, mainly to avoid the carbon-containing gas-filled rod from contacting the high-temperature melt to cause the melt to increase carbon, because the carbon added by the melt will combine with Mn and Fe to form a needle-like phase structure, increasing the number and size of the needle-like phase structure.
[0019] (3) Casting: The casting temperature of the high manganese aluminum bronze of the present invention is controlled in the range of 1200-1250°C, and low-speed casting is adopted. The casting speed is controlled within 50 mm / min. Too fast a casting speed will result in a longer ingot liquid cavity, and the alloy melt cannot be fully compensated for shrinkage, thereby generating larger micropore defects. In addition, too fast a casting speed will make the κ phase coarse or even agglomerated, which will cause the comprehensive performance of the alloy to fail to meet the requirements.
[0020] (4) Insulation: The insulation temperature of the high manganese aluminum bronze of the present invention is controlled in the range of 1000-1200° C. to maintain the fluidity of the alloy liquid, promote ingot shrinkage compensation, and reduce loose structure and micropore defects.
[0021] Based on different applications, the ingot of high manganese aluminum bronze of the present invention can be processed into rods, wires or silk materials and applied to different scenarios.
[0022] Compared with the prior art, the present invention has the following advantages: the high manganese aluminum bronze alloy of the present invention mainly controls the element content in the copper matrix, controls the addition ratio of Al and Mn elements, and controls the average width of the needle-like phase structure in the alloy to be ≤1μm and the average length to be ≤20μm, thereby effectively improving the strength and hardness of the high manganese aluminum bronze alloy, and making the high manganese aluminum bronze alloy have both excellent corrosion resistance and impact toughness comprehensive performance. At the same time, the high manganese aluminum bronze alloy of the present invention can achieve tensile strength ≥750MPa, yield strength ≥400MPa, hardness (HBW2.5 / 187.5) ≥200, and impact toughness ≥7J / cm 2, 72 hours salt spray corrosion weight loss rate is less than 0.05% and other excellent properties. The high manganese aluminum bronze alloy of the present invention can be used as a component material in the field of marine engineering, and its excellent corrosion resistance can increase the service life of marine materials such as propellers. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is an optical microscope image of a cross section of a high manganese aluminum bronze alloy ingot sample of Example 14;
[0024] Figure 2 This is an optical microscope image of the cross section of the comparative alloy ingot sample. DETAILED DESCRIPTION
[0025] The technical solution of the present invention is clearly and completely described below through specific embodiments and drawings.
[0026] The present invention selects 20 embodiments and 1 comparative example, and the specific alloy compositions are shown in Table 1. The embodiments are all processed into ingots with different compositions by the preparation method of the present invention. The preparation process of the high manganese aluminum bronze ingot of the embodiment is: smelting → degassing → casting → insulation, which specifically includes the following steps:
[0027] (1) Smelting: Raw materials are prepared and proportioned according to the alloy chemical composition shown in Table 1. First, cryolite is covered with molten copper and then other raw materials except Al are added for smelting. The smelting temperature is 1250° C. to 1350° C. During the smelting process, 2 kg of sodium fluoride and calcium fluoride mixed salt is added every 30 minutes until the smelting is complete. Then the temperature is lowered to 1150° C. to 1250° C., Al blocks are added for smelting, and after the smelting is complete, the raw materials are stirred until uniform.
[0028] (2) Degassing: Use a boron nitride inflatable rod to inflate with nitrogen for more than 10 minutes;
[0029] (3) Casting: Cast the alloy at a temperature of 1200-1250°C at a speed of less than 50 mm / min;
[0030] (4) Insulation: Finally, the cast alloy ingot is insulated at a temperature of 1000-1200°C to obtain the desired sample.
[0031] The difference between the preparation process of the comparative example and the example is that the graphite inflation rod is used for inflation for 10 minutes, the casting speed is 60 min / min, and the other process steps are the same.
[0032] The obtained samples were evaluated for their properties under the following conditions. The test results are shown in Tables 2 and 3.
[0033] The room temperature tensile test is carried out in accordance with "GB / T 228.1-2021 Metallic Materials Tensile Test Part 1: Room Temperature Test Method" on an electronic universal mechanical properties testing machine to test tensile strength, yield strength and other properties.
[0034] Brinell hardness HBW2.5 / 187.5 is tested by Brinell hardness tester in accordance with GB / T 231.1-2018 "Brinell hardness test for metallic materials".
[0035] The impact toughness is tested using a V-notch on a pendulum impact testing machine in accordance with GB / T229-2020 "Impact Test".
[0036] The corrosion resistance test is carried out in a salt spray corrosion test chamber according to GB / T 10125-2021 "Artificial atmosphere corrosion test salt spray test". The test is carried out for 72 hours in a neutral atmosphere with a pH value of 6.5-7.2, and the weight loss rate after 72 hours of corrosion is calculated.
[0037] The size and number of micropores in the samples were observed using an optical microscope. 2 The number of micropores within the field of view is counted, and the size range (i.e., the diameter of the circumscribed circle of the micropores) within the area is counted.
[0038] Take the cross section of the sample, observe the size and quantity of the needle-like phase structure in the sample under a scanning electron microscope, and perform data statistics. The specific operation is as follows: along the cross section direction of the sample, take a 250μm×200μm (i.e., an area of 5×10 4 μm 2 ) as the basic unit to observe the needle-like phase structure; first count the number of needle-like phase structures, and then divide the total number by 5 and round it off to get the unit area (i.e. 1×10 4 μm 2 ) number; then the length and width (i.e. the maximum width perpendicular to the length direction) of each needle-like phase structure are measured, and the average value is calculated.
[0039] The cross-sectional optical microscope image of the high manganese aluminum bronze alloy ingot sample of Example 14 is shown in Figure 1 , the cross-sectional optical microscope image of the comparative alloy ingot sample is shown in Figure 2 .contrast Figure 1 and Figure 2 It can be seen that in the cross-sectional microstructure of the high manganese aluminum bronze alloy of the present invention, the average size of the needle-like phase is significantly smaller than that of the comparative alloy, and even no needle-like phase appears.
[0040] Take the cross section of the sample, observe the size of the κ phase in the sample under an optical microscope and perform data statistics. The specific operation is as follows: along the cross section direction of the sample, take a 250μm×200μm (i.e., an area of 5×10 4 μm 2 ) as the basic unit for observing the κ phase; firstly, the number of κ phases with a size (i.e., the diameter of the κ phase circumscribed circle) in the range of 0.1 to 10 μm within the region was counted, and then the number was divided by 5 to obtain the unit area (i.e., 1×10 4 μm 2 )The amount of κ phase within.
[0041] In summary, the present invention controls the composition and microstructure of high manganese aluminum bronze, thereby obtaining higher strength and hardness than the control group without control, while having excellent comprehensive properties of corrosion resistance and impact toughness, and can be used in the field of marine engineering.
[0042] Table 1 Alloy composition
[0043]
[0044] Table 2 Alloy microstructure
[0045]
[0046] Table 3 Alloy properties
[0047]
Claims
1. A high manganese aluminum bronze alloy, characterized in that: The aluminum bronze alloy contains Mn: 11.5-14.5wt%, Al: 7.0-8.5wt%, Fe: 2.5-4wt%, Ni: 1.5-2.5wt%, C≤0.03wt%, and the balance is Cu and inevitable impurities. In the cross-sectional microstructure of the aluminum bronze alloy ingot, the average width of the needle phase structure is ≤1μm, and the average length is ≤20μm.
2. A high manganese aluminum bronze alloy according to claim 1, characterized in that: In the cross-sectional microstructure of the aluminum bronze alloy ingot, the number of needle-like phase structures per unit area is ≤5 / 1×10 4 μm 2 .
3. The high manganese aluminum bronze alloy according to claim 1, characterized in that: The mass percentage ratio of Al to Mn in the aluminum bronze alloy is Al / Mn:1:(1.62-1.86).
4. The high manganese aluminum bronze alloy according to claim 1, characterized in that: The aluminum bronze alloy also contains at least one element of Cr, S, Si, Pb, O, P, Ti, Zr, Co, B, Mg, Ag, Zn and RE in a total amount not exceeding 2wt%.
5. The high manganese aluminum bronze alloy according to claim 1, characterized in that: The cross-sectional microstructure of the aluminum bronze alloy ingot mainly contains α phase, β phase and κ phase, wherein the number of κ phases with a size between 0.1 and 10 μm is ≥50 / 1×10 4 μm 2 .
6. The high manganese aluminum bronze alloy according to claim 1, characterized in that: In the cross-sectional microstructure of the aluminum bronze alloy ingot, the micropore size is ≤0.2mm, and the number of micropores per unit area is ≤5 / mm 2 .
7. The method for preparing the high manganese aluminum bronze alloy according to any one of claims 1 to 6, characterized in that: The process flow of preparing the aluminum bronze alloy ingot includes: smelting→degassing→casting→heat preservation, wherein the casting speed is controlled within 50 mm / min, and a carbon-free gas-filled rod is used for degassing.
8. The method for preparing the high manganese aluminum bronze alloy according to claim 7, characterized in that: The degassing time shall not be less than 10 minutes.